Detection of SARS-CoV-2 IgG antibodies and inflammatory cytokines in saliva-a pilot study - S. Wadhwa; A.J. Yoon; K. Kister; I. Bolin; N. Chintalapudi; A. Besmer; A. Cantos; J. Shah; S.K. Gaitonde; S.W. Granger; C. Bryce; R. Fischer; et al. (Elsevier, 2023)
Objective: The pandemic caused by SARS-CoV-2 virus continues to have a profound effect worldwide. However, COVID-19 induced oral facial manifestations have not been fully described. We conducted a prospective study to demonstrate feasibility of anti-SARS-CoV-2 IgG and inflammatory cytokine detection in saliva. Our primary objective was to determine whether COVID-19 PCR positive patients with xerostomia or loss of taste had altered serum or saliva cytokine levels compared to COVID-19 PCR positive patients without those oral symptoms. Our secondary objective was to determine the correlation between serum and saliva COVID-19 antibody levels. Materials and methods: For cytokine analysis, saliva and serum were obtained from 17 participants with PCR-confirmed COVID-19 infection at three sequential time points, yielding 48 saliva samples and 19 paired saliva-serum samples from 14 of the 17 patients. For COVID-19 antibody analyses, an additional 27 paired saliva-serum samples from 22 patients were purchased. Results: The saliva antibody assay had 88.64% sensitivity [95% Confidence Interval (CI) 75.44%, 96.21%] to detect SARS-CoV-2 IgG antibodies compared to serum antibody. Among the inflammatory cytokines assessed - IL-6, TNF-α, IFN-γ, IL-10, IL-12p70, IL-1β, IL-8, IL-13, IL-2, IL-5, IL-7 and IL-17A, xerostomia correlated with lower levels of saliva IL-2 and TNF-α, and elevated levels of serum IL-12p70 and IL-10 (p < 0.05). Loss of taste was observed in patients with elevated serum IL-8 (p < 0.05). Conclusions: Further studies are needed to construct a robust saliva-based COVID-19 assay to assess antibody and inflammatory cytokine response, which has potential utility as a non-invasive monitoring modality during COVID-19 convalescence.